Energy commodities, precious metals and industrial metal markets: A nexus across different investment horizons and market conditions. (March 2021) - Rehman, Mobeen Ur; Vo, Xuan Vinh
Abstract: We investigate the presence of returns integration between energy commodities, precious metal commodities, and industrial metal commodities. We sample WTI crude oil, WTI Brent oil, natural gas, gas oil, gasoline, diesel as energy commodities, gold and silver as precious metal commodities, and copper, aluminum, zinc and nickel as industrial metal commodities. The sampling period of our study is based on the daily frequency and ranges from July 31, 2000 to July 31, 2020. Our methodology comprises a novel quantile cross-spectral approach proposed by Barunık and Kley (2015), which is capable to identify varying magnitude of connectedness between any two returns under different market conditions. Furthermore, this approach provides results under a short-, medium- and long-run investment perspective. Our results highlight low to moderate level integration among three commodity classes in the short- and medium-run investment periods however coherence level increases in the long-run periods under bearish and normal market conditions. These results are important for investors in terms of the suitability of different commodities regarding different investment periods and dynamic market conditions. Highlights: We investigate the presence of returns integration between energy commodities, precious metals and industrial metal commodities. We identify varying magnitude of connectedness between any two returns under different market conditions. Furthermore, this approach provides results under short-, medium and long-run investment perspective. Our results highlight low to moderate level integration among three commodity classes in the short- and medium-run investment periods. All the three commodity classes exhibit high coherence level in long-run under bearish and normal market conditions.